Pengaruh Training Soft skill dan Komunikasi Terhadap Kinerja Karyawan UMKM di Cikarang - Aleng; Shima, Putri; Permatasari, Nur Intan (Jurnal Ekonomi Syariah Pelita Bangsa, 2023)
This study aims to analyze the influence of variables Training Softskill, and Communication on Employee Performance. The analysis method used in this study is to use saturated sampling techniques. The type of data used is primary data obtained through a structured form using a questionnaire filled out by 30 people in one of the MSMEs. The analysis has met the requirements of analysis based on normally distributed data and there is no multicollinearity problem. Based on the output table "COEFFICIENTS" in the section " COLLINEARITY STATISTICS" it is known the tolerance value for the Training soft skill variable (X1). and Communication (X2) is 0.861 greater than 0.10. While the VIF values for the variables Training Softskill (X1) and Communication (X2) are 1,161 < 10.00, then referring to the basis of decision making in the multicholinearity test it can be concluded that there are no symptoms of multicholinearity in the regression model. Keywords: Soft skill; Employee performance; Communication